ANALISIS KEBUTUHAN LUAS TERMINAL PENUMPANG TAHUN 2042 DI BANDAR UDARA BINAKA GUNUNGSITOLI SUMATERA UTARA - Sarah Matilda Sinaga; Fahrur Rozi; Siti Fatimah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Binaka Airport has a terminal area of 5,571 m2 which served departure and arrival terminals. In 2012 the number of Binaka passengers reached 207.553 people and experienced an increase in the number of passengers for 5 years until 2016 reaching 331.473. With the increasing number of passengers at Binaka Airport , the terminal area is less accommodating all passengers who will carry out flight activities so that an analysis of the needs of passenger terminal for the next 20 years. Forecasting the number of passengers for the next 20 years using the linear regression method. The results of passenger forecasting in 2042 use SPSS software analysis with a total of 1.076.089 passengers. With the number of transfer passengers as many as 108, the number of peak hour passengers 538 the number of peak hour passengers coming and departing is the same, which is 269. The number of peak hour passengers is used to calculate the analysis of terminal needs. With the total needs of the terminal area in 2042 covering an area of 1,956 m2. The direction of terminal development is carried out by expanding towards the right by adding a width dimension and also expanding towards the vertical, namely increasing the dimension of the terminal length. With the addition of dimensions of 1,956